Library Service Resilience During Crises A Strategic Management Approach - Begum, Ahmadi; Bansal, Aman; Dhawan, Aashim; Dhanraj, Nasa; Das, Prangya; Kumar, Pavan (Indian Journal of Information Sources and Services, 2025)
The protection and support of library services have emerged as critical factors of concern for information continuity and community support in an era of rising unpredictability marked by natural disasters, pandemics, and sociopolitical unrest. This paper seeks to develop an appropriate strategic management framework to bolster library service resilience in the face of crises. The model, CRLRM, which stands for Crisis-Responsive Library Resilience Model, proposes a risk assessment based on adaptive leadership, digital infrastructure, and community-centered engagement. It further details a five-tiered approach that includes: (1) Risk and Impact Analysis, (2) Resource Readiness Planning, (3) Strategic Communication, (4) Continuity of Digital and Physical Access, and (5) Recovery and Learning Integration. CRLRM emphasizes the need for proactive and agile planning as well as unrelenting service delivery amidst disruption. This approach supports libraries to not only endure crisis conditions, but also reinforce their strategic role as trusted and stable institutions in their communities. The paper combines real world insights and examples, management theory, and resilience building literature to showcase ready relevancy of the model in multiple library contexts.